MicroRNA-146a Regulates Perfusion Recovery in Response to Arterial Occlusion via Arteriogenesis - Heuslein, Joshua L.; McDonnell, Stephanie P.; Song, Ji; Annex, Brian H.; Price, Richard J. (Frontiers in Bioengineering and Biotechnology, 2018)
The growth of endogenous collateral arteries that bypass arterial occlusion(s), or arteriogenesis, is a fundamental shear stress-induced adaptation with implications for treating peripheral arterial disease (PAD). MicroRNAs are key regulators of gene expression in response to injury and have strong therapeutic potential. In a previous study, we identified miR-146a as a candidate regulator of vascular remodeling. Here, we tested whether miR-146a regulates in-vitro angiogenic endothelial cell behaviors, as well as perfusion recovery, arteriogenesis, and angiogenesis in response to femoral arterial ligation (FAL) in-vivo. We found miR-146a inhibition impaired endothelial cell tube formation and migration in-vitro. Following FAL, Balb/c mice were treated with a single, intramuscular injection of anti-miR-146a or scramble locked nucleic acid (LNA) oligonucleotides directly into the non-ischemic gracilis muscles. Serial laser Doppler imaging demonstrated that anti-miR-146a treated mice exhibited significantly greater perfusion recovery (16% increase) compared mice treated with scramble LNA. Moreover, anti-miR-146a treated mice exhibited a 22% increase in collateral artery diameter compared to controls, while there was no significant effect on in-vivo angiogenesis or muscle regeneration. Despite exerting no beneficial effects on angiogenesis, the inhibition of mechanosensitive miR-146a enhances perfusion recovery after FAL via enhanced arteriogenesis.